A method for maintaining the acceleration rate and increasing the energy of self-injected bunch due to the use of inhomogeneous plasma - Bondar, D.S.; Maslov, V.I.; Onishchenko, I.N. (Problems of Atomic Science and Technology, 2023)
The paper considers the process of excitation of a wakefield in a plasma by a laser pulse. The plasma density corresponds to the density of free electrons in the metal. A method is demonstrated for keeping self-injected bunch in the accelerating phase of the wakefield as laser pulse and bunch move in plasma with an increasing density gradient. Thus, the rate of acceleration of self-injected bunch is maintained and enhanced. Розглянуто процес збудження кільватерного поля в плазмі лазерним імпульсом. Густина плазми відповідає густині вільних електронів у металі. Продемонстровано метод утримання самоінжектованого згусткa у фазі прискорення кільватерного поля, коли лазерний імпульс і згусток рухаються в плазмі зі зростаючим градієнтом щільності. Таким чином, темп прискорення самоінжектованого згусткa зберігається.